2022
DOI: 10.1038/s41698-022-00251-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of gastric pre-cancerous and cancer lesions reveals cell lineage diversity and intratumoral heterogeneity

Abstract: Single-cell transcriptomic profiles analysis has proposed new insights for understanding the behavior of human gastric cancer (GC). GC offers a unique model of intratumoral heterogeneity. However, the specific classes of cells involved in carcinogenetic passage, and the tumor microenvironment of stromal cells was poorly understood. We characterized the heterogeneous cell population of precancerous lesions and gastric cancer at the single-cell resolution by RNA sequencing. We identified 10 gastric cell subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 45 publications
0
72
0
Order By: Relevance
“…Enrichment of these genes and an identified proximity to exhausted CTLs in lymphoid structures suggest that iCAFs can regulate lymphocyte function (24). found that diffuse gastric cancer tissues showed a high prevalence of iCAFs compared to intestinal gastric cancer tissues, and overall iCAF number increased in gastric cancer compared to normal tissue (23). The same study also found a correlation between iCAFs and pro-stemness of tumors, suggesting that these cells promote cancer stem cell formation.…”
Section: Fibroblasts and Endothelial Cellsmentioning
confidence: 84%
See 4 more Smart Citations
“…Enrichment of these genes and an identified proximity to exhausted CTLs in lymphoid structures suggest that iCAFs can regulate lymphocyte function (24). found that diffuse gastric cancer tissues showed a high prevalence of iCAFs compared to intestinal gastric cancer tissues, and overall iCAF number increased in gastric cancer compared to normal tissue (23). The same study also found a correlation between iCAFs and pro-stemness of tumors, suggesting that these cells promote cancer stem cell formation.…”
Section: Fibroblasts and Endothelial Cellsmentioning
confidence: 84%
“…Other stromal cells within the TME, like fibroblasts and endothelial cells, also likely play immunological roles in tumor progression. CAFs and endothelial cells have been found to play distinct roles in regulating the antitumor immune response and promoting cancer growth and metastasis (23,24,26,39). Epithelial cell responses to these various inflammatory signals have displayed mixed findings with regards to promotion and inhibition of tumor progression, especially when focusing on different time points of disease and distinct gastric cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations